Documentation of sediment core GeoB24009-1 - Thomas Westerhold (PANGAEA, 2024)
Field data: Core images of gravity corer sediments collected during project Kerguelen Plateau Sediment Drifts with RV Sonne Cruise SO272 in 2020. Images of core sections were assambled using custom made IGOR Pro Software Code. The gravity cores were retrieved from the Labuan and Gaggatt Basin spanning Plio-Pleistocene to Eocene sediments. Core Images were generated to characterise the color of the sediment and document changes in color as well as sedimentary structures.